Effect of micrometeorological parameters on aphid and white rust epidemiology under different row direction in oilseed Brassica - GOYAL, AVINASH; DAS, D K; SEHGAL, V K; VASHISTH, ANANTA; MUKHERJEE, JOYDEEP (The Indian Journal of Agricultural Sciences, 2017)
Globally rapeseed-mustard (Brassica spp.) is a major oilseed crop. India is the second largest cultivator of mustard followed by China. The oilseed production increased significantly after yellow revolution but increasing population made pressure on production. The major losses in mustard yield occurs due to the attack of different pest and diseases. An option to minimize the losses in production of oilseed Brassica can be the suppression of the pest and disease incidence through modification of microclimate by altering the crop row direction. This experiment was conducted to evaluate the impact of microclimate variability due to different crop row directions on pest and disease incidence. The pest and disease are highly sensitive to temperature and relative humidity (RH) within crop canopy environment. The two row direction treatment, i.e. North-South (N-S) and East-West (E-W) were studied at the experimental farm, ICAR-IARI, New Delhi during rabi season, 2013-14. Parameters like number of aphid per top 10 cm of main shoot, per cent disease index (PDI) of white rust, temperature and RH within crop canopy were recorded at regular interval. The result showed a significant higher value of mean profile temperature in N-S row direction as compared to E-W row direction and an opposite trend was found for RH. Aphid infestation and PDI for white rust infection in E-W direction were significantly higher by 36% and 11.44%, respectively over N-S direction. It was concluded that both aphid and white rust incidence were reduced in N-S direction due to microenvironment modification. Aphid population was found negatively correlated with mean profile temperature and positively correlated with RH..